MALE INFLAMMATORY BREAST CANCER-AN ANALYSIS - Alsalamah , Yasir Ahmed; Salati, Sajad Ahmad; AlSulaim , Lamees Sulaiman (Sanamed, 2024)
Inflammatory breast cancer in males is an uncommon but extremely aggressive form of the disease. It is often misdiagnosed as a benign skin disease since it manifests as erythema along the chest wall. The management guidelines are not specific, and treatment is based on the experiences of female cancer patients. Since there is limited information available about this illness, this review aims to fill that gap by conducting a thorough analysis of case reports published in peer-reviewed journals since 2000.